THE MAGNETOSTRATIGRAPHY AND A 1780 MA PALAEOMAGNETIC POLE FROM THE RED SANDSTONES OF THE VAZHINKA RIVER SECTION, KARELIA, RUSSIA - Pisarevsky S.A.; Sokolov S.J. (My University, 2001)
A palaeomagnetic study of the Vepsian sandstones of the upper part of the Shoksha Formation has revealed a stable remanence. Rock magnetic and mineralogical studies suggest diagenetic haematite as the main carrier of this remanence. Two magnetic polarities with a regular stratigraphic zonation have been found. The reversal test is positive. The tilt-corrected palaeomagnetic direction is: N = 36, D = 354.3°, I = 21.6°, k = 22.3, 95 = 5.2°. The corresponding palaeomagnetic pole of 39.7°N, 221.1°E (Dp = 2.9°, Dm = 5.5°) is proposed as a ‘key pole’ for 1790–1770 Ma for Fennoscandia.